2021
DOI: 10.32996/ijllt.2021.4.5.11
|View full text |Cite
|
Sign up to set email alerts
|

Saudi EFL Students’ Perceptions of Online English Achievement Exams in the Era of COVID-19

Abstract: Due to the COVID-19 pandemic, assessment and testing processes have been shifted to an online environment. Therefore, this unexpected shift requires more recent research in the field of online assessment. Based on this requirement, the present research aimed to explore female EFL students’ perceptions of an online English achievement exam by focusing on these dimensions: availability and accessibility, instructions, and mode of delivery. The participants were preparatory year students at the English Language I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In a literature review on online assessment methods used during the Covid-19 pandemic, we found that both students had problems with online testing systems, including technical problems and demanding access to necessary documents and materials in the system, and academics who had a lack of experience in online systems (e.g., Arslan, 2022;Ocak and Karakuş. 2021;Kılınç et al 2021;Aljohani et al 2021;Raje and Stitzel 2020;). Thus, it can be said that academics mostly preferred "homework" as a "security blanket."…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a literature review on online assessment methods used during the Covid-19 pandemic, we found that both students had problems with online testing systems, including technical problems and demanding access to necessary documents and materials in the system, and academics who had a lack of experience in online systems (e.g., Arslan, 2022;Ocak and Karakuş. 2021;Kılınç et al 2021;Aljohani et al 2021;Raje and Stitzel 2020;). Thus, it can be said that academics mostly preferred "homework" as a "security blanket."…”
Section: Discussionmentioning
confidence: 99%
“…The study results indicated that students' attitudes differed significantly by age and gender. Binnahedh (2022), Ayyoub & Jabali (2021), Rajeh et al (2022), Ahmet et al (2021), and Aljohani et al (2021 were other researchers dealing with online exams and found that university students generally had positive attitudes towards e-assessment methods including online tests, e-portfolios and blogs.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies in the Saudi EFL context focused on students' attitudes and use of online learning (Ali et al, 2023;Al Shammari, 2021;Almekhlafy, 2020;Anas, 2020). Other studies highlighted the challenges that students/teachers face (Ja'ashan, 2020; Mahyoob, 2020), the impact of online learning on students' motivation (Ali et al, 2023;Oraif & Elyas, 2021), anxiety (Mohammed & Mudhsh, 2021), students' perceptions towards online learning (Al-Nofaie, 2020;Al-Sofi, 2020;Aljohani et al, 2021), language strategies (Mohammed, 2021;Shamsan et al, 2021) and informal digital learning (Mohammed & Ali, 2021). However, the study of Saudi EFL students' online test anxiety has remained an unexplored area of research.…”
Section: Introductionmentioning
confidence: 99%